Alternate wetting and drying reaches180,000 ha of rice in Vietnam, reducing over 1 million tCO2 eq per year - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
Vietnam's Ministry of Agriculture and Rural Development has used IRRI andCCAFS research findings and institutionalized their recommendations for alternate-wetting-and-drying (AWD) in the national implementation plan for Vietnam's NDC in agriculture as well as technical guidelines for nationwide application.